Working Memory Capacity as a Factor Influencing the Relationship between Language Outcome and Rehabilitation in Mandarin-Speaking Preschoolers with Congenital Hearing Impairment - Lo, Ming; Chen, Pei-Hua (Frontiers in Psychology, 2017)
Memory processes could account for a significant part of the variance in language performances of hearing-impaired children. However, the circumstance in which the performance of hearing-impaired children can be nearly the same as the performance of hearing children remains relatively little studied. Thus, a group of pre-school children with congenital, bilateral hearing loss and a group of pre-school children with normal hearing were invited to participate in this study. In addition, the hearing-impaired participants were divided into two groups according to their working memory span. A language disorder assessment test for Mandarin-speaking preschoolers was used to measure the outcomes of receptive and expressive language of the two groups of children. The results showed that the high-span group performed as good as the hearing group, while the low-span group showed lower accuracy than the hearing group. A linear mixed-effects analysis showed that not only length of rehabilitation but also the memory span affected the measure of language outcome. Furthermore, the rehabilitation length positively correlated with the measure of expressive language only among the participants of the high-span group. The pattern of the results indicates that working memory capacity is one of the factors that could support the children to acquire age-equivalent language skills.